2021
DOI: 10.7565/ssp.v4.5284
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of Explanatory Study on Social, Economic and Political Dimensions of Nutritional Status of Children Aged Six to Sixty Months from Low Socio-Economic Strata in Kerala, India

Abstract: Background: Despite having better human development indicators, one-fifth of under-five children in Kerala are undernourished. The demographic, socio-economic, cultural and political transition in Kerala necessitates a revisit on the causes of undernutrition among children given that it tackled many of the immediate causes of undernutrition. The present study aims at the multi-dimensional factors' influence on nutritional status of children from low socio-economic strata in Kerala. Methods/Design: The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We employed multiple methods -survey, key informant interviews, secondary data analysis, document analysis, and eld notes in the study. The detailed methodology is discussed elsewhere [4]. The ndings of the survey and secondary data analyses are also been published in a series of publications [5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…We employed multiple methods -survey, key informant interviews, secondary data analysis, document analysis, and eld notes in the study. The detailed methodology is discussed elsewhere [4]. The ndings of the survey and secondary data analyses are also been published in a series of publications [5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…Screening was performed at each AWC to identify children belonging to low socioeconomic strata. The detailed sampling strategy and screening are described elsewhere (Jayalakshmi & Srinivasan, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that household wealth index was the most significant contributor to stunting, followed by mother's education and nutritional status. Jayalakshmi and Kannan [10] explored the social, economic, and political dimensions of undernutrition among children aged 6-60 months from low socio-economic households in Kerala. The study found that children below 5 years from low socio-economic backgrounds were at a higher risk of being undernourished, which can perpetuate the cycle of poverty and undernutrition.…”
Section: Introductionmentioning
confidence: 99%